Recent strategies to improve boron dipyrromethene (BODIPY) for photodynamic cancer therapy: an updated review - Kue, Chin Siang; Ng, Shie Yin; Voon, Siew Hui; Kamkaew, Anyanee; Chung, Lip Yong; Kiew, Lik Voon; Lee, Hong Boon (Royal Society of Chemistry, 2018)
BODIPYs are photosensitizers activatable by light to generate highly reactive singlet oxygen (1O2) from molecular oxygen, leading to tissue damage in the photoirradiated region. Despite their extraordinary photophysical characteristics, they are not featured in clinical photodynamic therapy. This review discusses the recent advances in the design and/or modifications of BODIPYs since 2013, to improve their potential in photodynamic cancer therapy and related areas.